2020
DOI: 10.1101/2020.02.01.930412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA GAS5 attenuates fibroblast activation through inhibiting Smad3 signaling

Abstract: Transforming Growth Factor β (TGF-β)-induced fibroblast activation is a key pathological event during tissue fibrosis. Long noncoding RNA (LncRNA) is a class of versatile gene regulators participating in various cellular and molecular processes. However, the function of lncRNA in fibroblast activation is still poorly understood. In this study, we identified growth arrest-specific transcript 5 (GAS5) as a novel regulator for TGF-β-induced fibroblast activation. GAS5 expression was downregulated in cultured fibr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The other primary gene expression signature of primed fibroblasts we observed was lower expression of several genes associated with activated fibroblasts (SPP1, SERPINE2, THBS1, TAGLN) (Hsia et al, 2016;Layton et al, 2020;Peyser et al, 2019;Sandberg et al, 2019), differentiation into myofibroblasts (MYL9, ACTA2, TPM2, POSTN) (Guerrero-Juarez et al, 2019;Hsia et al, 2016;Layton et al, 2020;Walker et al, 2019), and pathological fibrosis (GDF15, IGFBP7, GAS5) (L.-X. Liu et al, 2009;Radwanska et al, 2022;Tang et al, 2020) (Radwanska et al, 2022;Tang et al, 2020). This signature suggests that unactivated fibroblasts within the population are more likely to reprogram.…”
Section: Primed Cells In the Initial Population Have Measurable Gene ...mentioning
confidence: 78%
“…The other primary gene expression signature of primed fibroblasts we observed was lower expression of several genes associated with activated fibroblasts (SPP1, SERPINE2, THBS1, TAGLN) (Hsia et al, 2016;Layton et al, 2020;Peyser et al, 2019;Sandberg et al, 2019), differentiation into myofibroblasts (MYL9, ACTA2, TPM2, POSTN) (Guerrero-Juarez et al, 2019;Hsia et al, 2016;Layton et al, 2020;Walker et al, 2019), and pathological fibrosis (GDF15, IGFBP7, GAS5) (L.-X. Liu et al, 2009;Radwanska et al, 2022;Tang et al, 2020) (Radwanska et al, 2022;Tang et al, 2020). This signature suggests that unactivated fibroblasts within the population are more likely to reprogram.…”
Section: Primed Cells In the Initial Population Have Measurable Gene ...mentioning
confidence: 78%
“…As the key effector cells in the process of wound healing, fibroblasts exhibit excessive hypercellularity, increased migration and superabundant ECM accumulation during the formation of HS [23]. Dysfunction of lncRNAs may aggravate the progression of skin fibrosis [24,25]. Findings of this study demonstrated high level of INHBA-AS1 in hHSFs, and that INHBA-AS1 silencing exhibited efficiently the proliferation, migration and ECM synthesis in hHSFs via regulating miR-141-3p/ MCL1 axis.…”
Section: Discussionmentioning
confidence: 61%
“…There have been conflict and controversy about the role of LncRNAs in varieties of fibrogenesis. For example, some lncRNAs have been clarified to show anti-fibrosis effect in renal fibrosis [43], pulmonary fibrosis [44], skin fibrosis [45]. On the contrary, some lncRNAs are demonstrated to have pro-fibrosis characteristics in cardiac fibrosis [46], liver fibrosis [47], skeletal muscle fibrosis [48].…”
Section: Discussionmentioning
confidence: 99%